Diversity in medical school admission: Insights from personnel recruitment and selection - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2015)
This issue of Medical Education includes four papers that focus upon recruitment and selection. My personal involvement with this field has occurred through my research on situational judgement tests (SJTs), most of which has been conducted in the broader field of personnel recruitment and selection for the workforce. As such, I read the four studies with two questions in mind: (i) on what issues have the respective strands of recruitment and selection diversity research in the medical education and workforce domains converged? (ii) What new insights emerging from workforce diversity can inform medical education research?